Hesitancy Toward the First COVID-19 Vaccine Booster Dose: A Cross-Sectional Study in Morocco - Fatima Zahra Chellat; Nassiba Bahra; Zakia Marsou; Marwa El Baldi; Soumaya Benmaamar; Nabil Tachfouti; Nada Otmani; Mohamed Berraho; Karima El Rhazi (Journal of Primary Care & Community Health)
Background: The COVID-19 pandemic has posed significant global health challenges, requiring mass vaccination to reduce severe illness and mortality. Despite strong evidence supporting booster dose safety and efficacy, uptake remains low due to widespread hesitancy. This study aims to comprehensively explore the factors contributing to first COVID-19 booster vaccine hesitancy among the general population in Morocco. Methods: A cross-sectional study was conducted among 574 participants from primary healthcare centers in Fez, Morocco, between April 2022 and April 2023. Data were collected using a structured questionnaire based on the WHO SAGE framework, assessing socio-demographic, contextual, individual, group, and vaccine-specific determinants. Statistical analyses included chi-squared tests and multivariate logistic regression ( P  < .05). Results: Hesitancy toward the first booster dose was reported by 66.2% of participants. Vaccine-specific concerns were the strongest predictor (Adjusted Odds Ratio [AOR] = 27.6; 95% Confidence Interval [CI] = [11.1-68.3]; P  < .001), followed by contextual factors (AOR = 7.8; 95% CI = [4.0-15.4]; P  < .001) and individual/group determinants (AOR = 3.0; 95% CI = [1.6-5.6]; P  = .001). Younger age (<46 years, AOR = 3.0) and lower income (AOR = 5.9) also increased hesitancy. Conclusion: Booster dose hesitancy in Morocco is driven by vaccine-specific concerns, contextual influences, and individual beliefs. Addressing these factors through targeted communication, trust-building strategies, and inclusive public health policies is essential to increase booster uptake and strengthen national pandemic response efforts.